High-performance thin film composite nanofiltration membranes with HOF-21 interlayer - Wang, Jian; Xu, Hang; Wang, Ao; Ding, Mingmei; Hu, Tianlong; Wang, Jingjun; Pan, Yang (Desalination, 2025)
Hydrogen-bonded organic frameworks (HOF) possess desirable properties such as intrinsic, modifiable, and uniform pore structures, making them highly promising materials for molecular separation. However, their application in membrane technology remains underexplored. This study successfully fabricated a novel interlayered thin-film nanocomposite (ITFN) membrane, using HOF material as the intermediate layer. The HOF-21 interlayer facilitated hydrogen bonding with piperazine, retarding amine monomer diffusion and resulting in a thinner, denser polyamide (PA) selective layer. The interconnected, uniformly sized pores of the HOF-21 nanoparticles yielded ultra-thin ITFN membranes with a highly ordered three-dimensional porous architecture. The study demonstrates that the new ITFN membranes are successfully prepared, and the PA layer of the membrane presents a wrinkled structure, and the cross-linking enhancement results in the improvement of the membrane performance. Consequently, the ITFN membrane demonstrates a high water flux (36.44 L m−2 h−1 bar−1), coupled with a large Na2SO4 rejection rate (97.06 %). The study establishes a foundation for advancing HOF membranes in liquid-phase molecular separation, thereby broadening the potential applicability of HOF materials across diverse domains. [Display omitted] •HOF-21 was used to prepare ITFN membrane.•The special mechanism of the HOF-21 interlayer was discussed.•The TFNi membrane exhibit high water flux and unchanged high salt rejection.•The simple preparation conditions of HOF-21 facilitated the practical application of ITFN.